Noncovalent structure of SENP1 in complex with SUMO2 - Ambaye, Nigus D. (Acta crystallographica. Section F, Structural biology communications, 2019)
SUMOylation is a post‐translational modification in which a small ubiquitin‐like molecule (SUMO) is appended to substrate proteins and is known to influence myriads of biological processes. A delicate interplay between several families of SUMOylation proteins and their substrates ensures the proper level of SUMOylation required for normal cell function. Among the SUMO proteins, SUMO2 is known to form mono‐SUMOylated proteins and engage in poly‐SUMO chain formation, while sentrin‐specific protease 1 (SENP1) is a key enzyme in regulating both events. Determination of the SENP1–SUMO2 interaction is therefore necessary to better understand SUMOylation. In this regard, the current paper reports the noncovalent structure of SENP1 in complex with SUMO2, which was refined to a resolution of 2.62 Å with R and Rfree values of 22.92% and 27.66%, respectively. The structure shows that SENP1–SUMO2 complex formation is driven largely by polar interactions and limited hydrophobic contacts. The essential C‐terminal motif (QQTGG) of SUMO2 is stabilized by a number of specific bonding interactions that enable it to protrude into the catalytic triad of SENP1 and provide the arrangement necessary for maturation of SUMO and deSUMOylation activity. Overall, the structure shows a number of structural details that pinpoint the basis of SENP1–SUMO2 complex formation. The complex of two key proteins of the SUMOylation pathway is presented to 2.6 Å. This work reveals the polar nature of the interaction between the proteins, and shows how the essential QQTGG motif of SUMO2 is arranged relative to the active site of SENP1.